2004
DOI: 10.1103/physrevlett.92.195704
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Condensation in Linear Mesopores of Different Shape

Abstract: The hysteresis and kinetics of capillary condensation of N2 and Ar in linear mesopores, produced by etching of Si wafers, have been studied for different pore shapes, including the ink bottle geometry. Pore blocking has been observed in the solid state of the pore fillings, but not in the liquid state. We conclude that individual local geometries such as the pore mouth, a blind end, or a single constriction have no effect on the shape of sorption isotherms, that the pore space should be regarded as a statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

29
210
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(245 citation statements)
references
References 24 publications
29
210
2
Order By: Relevance
“…Mean density functional theory 15 , molecular dynamics simulations of adsorption and desorption by diffusive mass transfer into model pores 16 and grand canonical Monte Carlo simulations 17 confirm this classical picture of adsorption in a single pore. In contrast to theoretical predictions, experiments with mesoporous matrices characterized by a trivial porous network topology consisting of straight and not interconnected pores show that adsorption is always characterized by pronounced hysteresis loops independent of whether the pores are open at one or at both ends 7,12,[18][19][20][21] . In other words, in these materials the pores appear not to be independent during an adsorption isotherm.…”
mentioning
confidence: 61%
“…Mean density functional theory 15 , molecular dynamics simulations of adsorption and desorption by diffusive mass transfer into model pores 16 and grand canonical Monte Carlo simulations 17 confirm this classical picture of adsorption in a single pore. In contrast to theoretical predictions, experiments with mesoporous matrices characterized by a trivial porous network topology consisting of straight and not interconnected pores show that adsorption is always characterized by pronounced hysteresis loops independent of whether the pores are open at one or at both ends 7,12,[18][19][20][21] . In other words, in these materials the pores appear not to be independent during an adsorption isotherm.…”
mentioning
confidence: 61%
“…On the one hand, this matrix allows one to study the influence of spatial confinement on the physics and chemistry of liquids [9][10][11][12][13][14][15]. On the other hand, it is possible to synthesize composite materials with finely tuned optical and electrical properties by liquid adsorption or infiltration [4,16].…”
mentioning
confidence: 99%
“…Experimental studies have shown conflicting results: for example isotherms in aluminium and silicon adsorbents with closed end pores exhibit hysteresis loops (Bruschi et al, 2008;Coasne et al, 2002;Wallacher et al, 2004). However, these real materials may have irregularities on the surface that could be responsible for the hysteresis (Bruschi et al, 2008;Puibasset, 2009).…”
Section: Introductionmentioning
confidence: 95%
“…The drive to improve our understanding of the microscopic origin of hysteresis has been greatly facilitated by the synthesis of ordered mesoporous solids and advances in computer simulation (Horikawa et al, 2011). Several attempts have been made to tailor adsorbent solids in order to study the dependence of hysteresis on pore structure, for example by synthesising pores with either open ends, or with one end closed, or pores with narrower openings to the surrounding gas (Bruschi et al, 2008;Bruschi et al, 2010;Wallacher et al, 2004). In particular, the possible existence of hysteresis in closed end pores has been a controversial topic that has important consequences for more complex materials where pore cross sections may vary from place to place.…”
Section: Introductionmentioning
confidence: 99%